Global Supply Chain Disruptions : Competition Policy Implications - World Bank (Washington, DC, 2022)
This note complements prior World Bank work analyzing the technical drivers of supply chain disruptions from 2021 onwards. The focus of this note is to shed light on the role of market structure and dynamics by: (a) analyzing how market dynamics and industry structure may have contributed to the current situation; (b) outlining implications for value chains in developing countries; and (c) suggesting further policy and research priorities. On the demand side unexpected demand spikes in the United States have created disruptions due to the sheer volume of logistics throughput needed and the sudden, unexpected rebound in demand that is contributing to the “bullwhip effect.” On the supply side, capacity constraints with respect to port-hinterland connections have been the main bottleneck rather than maritime shipping per se. However, this note raises the concern that industry structure and alliance practices within the maritime shipping, shipbuilding, and container manufacturing sectors may be contributing to the extreme reaction of shipping prices. In the short term, policy makers in developing countries can help mitigate the effects of rising shipping costs and decreasing service levels by extending the timeframes of trade finance and removing barriers to overland trade. Although there is little that governments outside of China, Europe, and the United States can do to directly solve the process bottlenecks, market characteristics suggest that the global logistics industry may be susceptible to collusive outcomes, which exacerbate price spikes. Thus, governments could pay closer attention to potential anticompetitive behavior, especially in maritime shipping and hinterland logistics. In the medium to long term, policy makers, regulators, and researchers should more carefully consider efficiency–resilience tradeoffs in the global logistics industry. Key topics to explore include investigations into potential anticompetitive behavior by shipping lines and increased scrutiny over mergers and alliance practices among logistics service providers and the supplying manufacturing industries. Public-private and private initiatives to facilitate data sharing may also help improve forecasting, which could help mitigate the effects of demand volatility. This note was predominantly prepared before the invasion of Ukraine by the Russian Federation, which started in February 2022. In the short term, the war is likely to exacerbate the congestion at European ports and disrupt Asia-Europe rail links, potentially leading to higher shipping prices. In the long term, it remains to be seen whether decreases in global demand due to the war will lower shipping demand and prices. Nevertheless, the long-term structural constraints to competition in the sector highlighted in this note remain the same overall.